Morphometric profile of large intestinal neuronal plexuses in normal perinatal autopsies and Hirschsprung disease. Issue 3 (12th September 2016) - Subramanian, H.; Badhe, B. A.; Toi, P. C.; Sambandan, K.
Abstract: Objectives: To derive objective values for the diagnosis of Hirschsprung disease (HSCR) from a comparison of the morphometric profile of large intestinal neuronal plexuses in normal perinatal autopsies and surgical specimens of HSCR. Methods: A cross‐sectional comparative study with 40 subjects each in (i) non‐HSCR perinatal group encompassing neonates and stillborn babies beyond 30 weeks of gestation on whom autopsies were conducted and (ii) HSCR group comprising all patients clinicoradiologically diagnosed as HSCR. The morphometric assessment was done on hematoxylin‐and‐eosin‐stained sections. Key Results: The morphometric profile in terms of average number of ganglia/linear mm of colon, interganglion distance, number of ganglion cells/ganglion, average ganglion cell length, ganglion cell nuclear area, ganglion cell nuclear diameter, nerve trunk thickness, and density has been outlined. On comparison with the neuroanatomically normal zone of HSCR, the cut‐offs to identify hypertrophic nerve trunks (nerve trunk thickness of >37.85 μm) and reduced number of ganglia (number of ganglia/linear mm of colon <2.05 and interganglion distance of >229 μm) were derived. Conclusions & Inferences: The determined objective values, after testing on diagnostic rectal biopsies, may serve to formulate a diagnostic algorithm along with immunostaining for diagnosis of HSCR in colorectal specimens. Abstract : Morphometric assessment of neuronal plexuses with image capture and analysis in 40 normal and 40 Hirschsprung colons was used to derive objective reference values based on clearly defined evaluation techniques.